9a2b2-12ab3= вынести общий множитель
20x3y2+4x2y=
7a2bc+14ab2c=
9xyz2-12xy2z=
6y5+12y4-3y3=
20a4-5a3+15a5=
4a2b2+36a2b3+6ab4=
2x2y4-2x4y2+6x3y3=
разложите на множители
a(m+n)+b(m+n)=
b(a+5)-c(a+5)=
a(b-5)-(b-5)=
(y-3)+b(y-3)=
2a(a-b)+3b(a-b)=
5a(x+y)-4b(x+y)=
7a(c-d)-2b(c-d)=
a2(x-y)+b2(x-y)=
a2(x+y)-b2(x+y)=
a(x2-y2)-b(x2+y2)=
x(a2-2b2)+y(a2-2b2)=
(x-3)(2x+4)=0⇒ 1)x=3 2)2x+4=0 x=-2
2.(3x-1)( x-5)-2( x+5)=0
3x²-x-15x+5-2x-10=0 3x²-18x-5=0
1)x1 ={9-√(81+15)}/3 2) x1 ={9+√(81+15)}/3
если не допущена ошибка...
3.(x-3)(x+3)=5x-13
x²-9-5x+13=0 x²-5x+4=0 1) x1=4 2)x2=1
4.( x+4(2x-1)= x(3 x+11)
9x-4 = 3x²+11x 3x²+2x +4=0 D= 4-4·3·4<0
НЕТ РЕШЕНИЙ
5.- x(4x +1)=( x+2)( x-2)
-4x²-x=x²-4 5x²+x-4 = 0 D= 1-4·5(-4)=81
1)x1=( -1-9)/10 x1=-1 2)x2=( -1+9)/10 x1=0.8
6. 7(1- x)=(2x+3)(1- x) (7-2x-3)(1- x)=0 1)x1=2 2)x=1